Mighty Meg and the magical ring - Griffin, Sammy (Griffin, Sammy. Mighty Meg, 2019)
Eight-year-old Meg's life is turned upside-down when the ring she received from her Aunt Nikki, an archaeologist, gives her superpowers, but can she find the courage to be the superhero her town needs?